Next-Gen Teacher Growth: Exploring Online Professional Development - Yunos, Farah Naaz Abd; Singh, Gurdip Kaur Saminder; Kumar, Menaga; Hanefar, Shamsiah Banu Mohamad; Faizuddin, Ahmad (Journal of Ecohumanism, 2024)
The current study explores perceptions and effectiveness of online professional development (OPD) opportunities at higher education institution, thus closing a substantial gap in current literature about the OPD preferences among English as a second language (ESL) lecturers. Professional development is a cornerstone approach to enhancing teacher competence and has gradually moved from traditional face-to-face sessions to online platforms particularly during the COVID-19 pandemic. Although vast research is available on teacher professional development in Malaysia, study into the experiences of language lecturers at higher education institutions with OPD remains scant. This qualitative study which involved seven lecturers from a private university utilized semi-structured interviews to obtain fuller narratives of their perceptions of OPD. In general, findings indicated that although most lecturers had little experience of online professional learning, they held a positive attitude to the possible benefits it could offer. Further analysis identified four major themes for discussion, namely the relevance and effectiveness of OPD, the role of facilitators in enhancing OPD outcomes, the importance of classroom engagement and interaction, as well as professional development effectiveness and growth through OPD. The findings from the study highlighted the usefulness, trials, and room for improvement within OPD programs and suggests that future initiatives should be specifically tailored to consider the ever-evolving needs of diverse groups of teachers in order to maximize the effectiveness of any professional development initiative.